Use of Sandwich-Cultured Human Hepatocytes to Predict Biliary Clearance of Angiotensin II Receptor Blockers and HMG-CoA Reductase Inhibitors - Abe, Koji; Bridges, Arlene S.; Brouwer, Kim L.R. (Drug metabolism and disposition, 2009)
Previous reports have indicated that in vitro biliary clearance (Clbiliary) determined in sandwich-cultured hepatocytes correlates well with in vivo Clbiliary for limited sets of compounds. The purpose of this study was 1) to determine the in vitro Clbiliary in sandwich-cultured human hepatocytes of angiotensin II receptor blockers and HMG-CoA reductase inhibitors that undergo limited metabolism and 2) to compare the predicted Clbiliary values with estimated in vivo hepatic clearance data in humans. The average biliary excretion index and in vitro intrinsic Clbiliary values of olmesartan, valsartan, pravastatin, rosuvastatin, and pitavastatin in sandwich-cultured human hepatocytes were 35, 23, 31, 25, and 16%, respectively, and 0.943, 1.20, 0.484, 3.39, and 5.48 ml/min/kg, respectively. Clbiliary values predicted from sandwich-cultured human hepatocytes correlated with estimated in vivo hepatic clearance values based on published data (no in vivo data in humans was available for pitavastatin), and the rank order was also consistent. In conclusion, in vitro Clbiliary determined in sandwich-cultured human hepatocytes can be used to predict in vivo Clbiliary of compounds in humans.